The influence of proton pump inhibitors on the effect of clopidogrel on the risk of recurrent ischemic stroke - Endang Mahati; Jarir Atthobari; . Ngatidjan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Patients surviving with a stroke have an increased risk for recurrent stroke. Clopidogrel iswidely used to prevent recurrent stroke. However, clopidogrel may cause gastrointestinalbleeding (GIB). Therefore, proton pump inhibitors (PPIs) is recommended to reduce theside effect of clopidogrel. Unfortunately, these both drugs are metabolized in the liverby the same enzyme i.e. cytochrome P4502C19 (CYP219) that may reduce the effectof clopidogrel. The aim of this study was to evaluate the influence of PPIs on the effectof clopidogrel in the prevention of recurrent stroke. It was a hospital-based case controlstudy conducted in Bethesda Private Hospital, Yogyakarta involving 392 patients withrecurrent stroke as cases and 784 patients with first-ever stroke as controls. The exposureof PPIs during clopidogrel therapy on both cases and controls groups were recordedfrom prescription records for at least six months before index date. The duration of PPIsexposure were categorized as current expoure (less than two months before the indexdate) and recent exposure (2-6 months before the index date). The result showed therewas no influence of PPIs exposure on the effect of clopidogrel on the risk of recurrentischemic stroke (OR: 1.00; 95% CI: 0.56-1.79). Moreover, the current use of PPIs andclopidogrel could decrease the risk of recurrent ischemic stroke (OR: 0.04; 95% CI:0.01-0.41). In conclusion, there is no association between PPI exposure and the risk ofrecurrent stroke in patients receiving clopidogrel.